Maternal Outcome in Pregnant Patients with Abruptio Placentae at Mardan Medical Complex - Mahmood, Sadia; Akhtar, Tayyaba; Amin, Nuzhat; Jamal, Sundas (Indus Journal of Bioscience Research, 2025)
Background: Abruptio placentae remains a major cause of obstetric morbidity, especially in developing regions. Prompt diagnosis and risk stratification are essential for reducing maternal complications. Understanding demographic and clinical predictors can improve outcomes and resource allocation in tertiary care settings. Objective: To evaluate maternal outcomes in pregnant women diagnosed with abruptio placentae and to assess associations with demographic and clinical risk factors. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from August 2024 to February 2025 at the Department of Obstetrics and Gynecology, Mardan Medical Complex, Mardan. Methodology: A total of 157 pregnant women aged 18–40 years with gestational age >26 weeks and ultrasound-confirmed abruptio placentae were enrolled. Maternal complications including blood transfusion (≥8 units), postpartum hemorrhage (>500 mL), and acute kidney injury were recorded. Data were analyzed using SPSS v21. Chi-square and Fisher’s exact tests were used to explore associations with risk factors such as age, BMI, diabetes, hypertension, and socioeconomic status. Results: The mean maternal age was 29.87±5.52 years and gestational age was 31.70±3.26 weeks. Blood transfusion was required in 80.3% of cases, postpartum hemorrhage occurred in 49.7%, and 5.1% developed acute kidney injury. Conclusion: Abruptio placentae remains a serious obstetric emergency linked to increased maternal morbidity. Key risk factors include high BMI, advanced age, hypertension, and diabetes. Lower socioeconomic status heightens vulnerability, underscoring the need for early diagnosis, risk stratification, and improved antenatal care access.